2017
DOI: 10.3892/or.2017.5422
|View full text |Cite
|
Sign up to set email alerts
|

First description of a double heterozygosity for BRCA1 and BRCA2 pathogenic variants in a French metastatic breast cancer patient: A case report

Abstract: Hereditary breast and ovarian cancer syndrome is an autosomal dominant disease caused primarily by germline mutations in the BRCA1 or BRCA2 gene. Rare cases of double heterozygosity for BRCA1 and BRCA2 mutations have been reported quite exceptionally in non-Ashkenazi individuals. We describe the case of a woman who developed a bilateral breast cancer, discovered concomitantly, at 46 years old. Biopsies confirmed the presence of two breast cancers with distinct histology. BRCA analysis was tested due to a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In two papers we have amended the calculation of two patients ( Table 1 ) [ 17 , 18 , 19 ]. From 1998 to 2017, 19 articles described 33 families with 54 subjects carrying a double BRCA mutation [ 2 , 8 , 9 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Table 1 summarizes the main data, including ethnicity, description of mutations, matrilineal or patrilineal transmission of variants, cancer type and age of onset, for a total of 56 cases (34 probands and 22 relatives), with the addition of our current report.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In two papers we have amended the calculation of two patients ( Table 1 ) [ 17 , 18 , 19 ]. From 1998 to 2017, 19 articles described 33 families with 54 subjects carrying a double BRCA mutation [ 2 , 8 , 9 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Table 1 summarizes the main data, including ethnicity, description of mutations, matrilineal or patrilineal transmission of variants, cancer type and age of onset, for a total of 56 cases (34 probands and 22 relatives), with the addition of our current report.…”
Section: Resultsmentioning
confidence: 99%
“…In this population, three founder mutations, BRCA1 185delAG, BRCA1 5382insC and BRCA2 6174delT, are particularly common with an approximate frequency of 1%, 0.1%, and 1.4%, respectively [ 6 , 7 , 43 ]. Therefore, on the basis of predictive statistical calculations, the population carrier frequency of BRCA1 and BRCA2 mutations in the Ashkenazi population should be approximately 3%, with a presumable occurrence of double heterozygosity of 1 in 1800 individuals [ 8 , 9 ]. In a BRCA1 and BRCA2 mutational study performed on 10,000 subjects, including 3022 Ashkenazi, Frank et al, identified double mutations exclusively in the Ashkenazi population with a frequency of 11 of the 3022 tested individuals (0.36%), and 11 on 617 positive cases (1.8%) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other risk factors appear to be specific to non-menopausal female patients (13). Furthermore, a study published in 2006 suggested that the recent use of oral contraceptives, particularly in young nulligravidae was associated with an increased risk of breast cancer prior menopause (14). While obesity is a recognized risk factor in post-menopausal patients, it can function as a protective factor in young female patients (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study published in 2006 suggested that the recent use of oral contraceptives, particularly in young nulligravidae was associated with an increased risk of breast cancer prior menopause (14). While obesity is a recognized risk factor in post-menopausal patients, it can function as a protective factor in young female patients (13,14). The risk of breast cancer is also higher in young female patients of African descent, compared with in Caucasian female patients, as has been demonstrated in the USA (15).…”
Section: Discussionmentioning
confidence: 99%